COVID-19, the Great Recession and Young Adult Identity Development : Shock-Sensitive Dynamic Ecological Systems Theory - Nichols Lodato, Bronwyn (New York : Routledge, 2024)
This book offers a paradigm shift in the framing of identity development by advancing a new, shock-sensitive framework for diverse young adult identity development after high school. The author builds on the critical theoretical contributions of Urie Bronfenbrenner and Margaret Beale Spencer that highlight the person-context nature of development and the dynamic nature of vulnerability, risk, and coping. The inclusive, policy-relevant theoretical approach emerges from the author's mixed-methods study that examines the context-dependent identity development experiences of young adults. The book also accounts for the unique person-context dynamics during the Great Recession and COVID-19 global shocks that drive how diverse young adults make meaning of risk as they cope with the shock-related disruptions on their individual postsecondary journeys toward building their adult identities. Given that the qualitative interview component of the study occurred during the COVID-19 pandemic, this research offers a unique, in-real-time vantage point from participants who are making meaning of their choices and decisions as the shock was underway. The book also tracks the heightened importance of online tools during this period and the implications of virtual contexts where developmental activities are pursued, such as online education, work, and socializing. Advancing a new, shock-sensitive, interdisciplinary theory of identity development in postsecondary journeys of diverse young adults, it will appeal to scholars and students at the graduate level working across psychology, human development, educational psychology, sociology of education, and public policy.
1. What happens when the world stops? 2. The Role of Education in Society 3. Identity Development and Postsecondary Education 4. Study Design and Implementation 5. (Un)Stable Paths: Postsecondary Enrollment Experiences through the Great Recession and COVID-19 6.Dynamic Ecological Systems Theory of Identity Development--A New Paradigm of Shock--Informed Young Adult Identity Development Research
Keywords: Young adults -- Psychology; Identity (Psychology); COVID-19 Pandemic, 2020- -- Influence; PSYCHOLOGY / General; PSYCHOLOGY / Developmental / Adolescent